2005
DOI: 10.1177/0002764205279419
|View full text |Cite
|
Sign up to set email alerts
|

A Typology for the Study of Entertainment Television and Politics

Abstract: General questions concerning the role of entertainment media in politics permeated the 2004 election cycle. Political communication scholars are beginning to systematically analyze potential sociopolitical ramifications stemming from entertainment television viewing, but one difficulty with this emerging area of research is an inability to forge connections between seemingly disparate research agendas. Several distinct lines of research are summarized in this article and forged into a coherent whole through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
98
0
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 58 publications
(57 reference statements)
2
98
0
13
Order By: Relevance
“…Studies show various forms of political entertainment media content impact the full range of the hierarchy of effects, including salience (e.g., Young, 2006), knowledge (e.g., Baum, 2003;Prior, 2003), perceptions (e.g., Holbert et al, 2007), attitudes (Holbert et al, 2003;Moy, Xenos, & Hess, 2005b), and behaviors (Cao & Brewer, 2008;Moy et al, 2005a). It is clear from this empirical research that political entertainment content has the ability to generate politically relevant outcomes (Holbert, 2005;Holbert et al, 2010).…”
Section: Political Tv Satirementioning
confidence: 78%
See 1 more Smart Citation
“…Studies show various forms of political entertainment media content impact the full range of the hierarchy of effects, including salience (e.g., Young, 2006), knowledge (e.g., Baum, 2003;Prior, 2003), perceptions (e.g., Holbert et al, 2007), attitudes (Holbert et al, 2003;Moy, Xenos, & Hess, 2005b), and behaviors (Cao & Brewer, 2008;Moy et al, 2005a). It is clear from this empirical research that political entertainment content has the ability to generate politically relevant outcomes (Holbert, 2005;Holbert et al, 2010).…”
Section: Political Tv Satirementioning
confidence: 78%
“…Many of the political entertainment exposure measures in these surveys reference late-night talk shows like Letterman or Leno in the same item as The Daily Show with Jon Stewart. Holbert (2005) has argued that it is important to distinguish between various types of political entertainment TV programming based on the degree to which (1) the political content is primary or secondary in the programming and (2) the outlet offers explicit versus implicit political messages. A big distinction between late-night talk shows like Leno and Letterman and a program like The Daily Show is that the percentage of any one episode of Leno or Letterman that deals squarely with politics is exceedingly low.…”
Section: Political Tv Satirementioning
confidence: 99%
“…Traditionally, research defined fake news as a television comedy genre in which a portion of the program is devoted to political satire [29]. Such programs draw millions of viewers by mimicking a traditional news cast, but adding humor [18,30].…”
Section: Fake Newsmentioning
confidence: 99%
“…This difference could result in different selection and processing patterns for health and political messages, respectively, which in turn shape entertainment-embedded persuasion effects. Additionally, political satire in particular may be rather implicit in its meaning and thus open to interpretations that suit the recipients (Holbert, 2005;LaMarre, Landreville, & Beam, 2009).Regardless of what persuasive outcome a political message embedded in entertainment pursues, there may be much to be learned from the research on health entertainment-education. To assess hopes that political messages might reach the electorate better when interjected in entertainment, it is worthwhile to inspect what health entertainment-education research has found.…”
mentioning
confidence: 99%